Endothelial Injury Syndromes after Allogeneic Hematopoietic Stem Cell Transplantation: Angiopetin-2 as a Novel Predictor of the Outcome and the Role of Functional Autoantibodies against Angiotensin II Type 1 and Endothelin A Receptor - Vythoulkas,D.; Lazana,I.; Kroupis, C.; Gavriilaki,E.; Konstantellos,I.; Bousiou,Z.; Chondropoulos,S.; Griniezaki,M.; Vardi,A.; Gkirkas,K.; Karagiannidou,A.; Batsis, I; et al. (Int.J.Mol.Sci., 2023)
Transplant-associated thrombotic microangiopathy (TMA) occurs in a significant percentage of patients after allogeneic stem cell transplantation (allo-SCT) and is associated with significant morbidity and mortality. The aim of the present study was to examine the association of serum angiopoetin-2 (Ang2) levels and the presence of antibodies against angiotensin II type 1 (AT1R) and ndothelin A Recreptor (ETAR) with the outcome of patients with TMA and/or graft-versus-host disease (GVHD) after allo-SCT. Analysis of our data showed that elevated serum Ang2 levels at the time of TMA diagnosis are significantly associated with increased non-relapse mortality and decreased overall survival. To our knowledge, this is the first study demonstrating an association between raised Ang2 levels and poor outcomes in patients with TMA. Antibodies against AT1R (AT1R-Abs) and ETAR (ETAR-Abs) were detected in 27% and 23% of the patients, respectively, but there was no association between the presence of autoantibodies and the outcome of patients with TMA. However, a significant finding was the strong positive correlation between the presence of AT1R-Abs with the occurrence of chronic fibrotic GVHD, such as scleroderma and cryptogenic organizing pneumonia, raising the possibility of the contribution of autoantibodies in the pathogenesis of fibrotic GVHD manifestations
Keywords: Adverse effects; Angiotensin II; Autoantibodies; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; metabolism; pathology; Peptide Hormones; Receptor,Angiotensin,Type 1; Receptor,Endothelin A